Prospective associations between peer functioning and social anxiety in adolescents: A systematic review and meta-analysis - Chiu, K; Clark, DM; Leigh, E (Elsevier, 2020)
Background During adolescence, peer relationships take precedence and there is a normative increase in social anxiety. Although prospective studies have suggested peer functioning and social anxiety can influence each other, their findings have not been examined systematically. We performed a systematic review and meta-analysis of prospective studies to examine the bidirectional relationship between peer functioning and social anxiety in adolescence.